Foundations of Christian thought and practice a model for replacing Old and New Testament surveys with an innovative approach to teaching religion in 21st century colleges and universities - Hudson, Don Michael; Roberts, Andy M. (2019)
Institutions of faith can no longer assume students of faith, and institutions of faith can no longer assume that a survey of the Old and New Testaments in today's college curriculum will provide the necessary elements to develop, sustain, and nurture biblical literacy in students. Nor can it be assumed that this antiquated model will equip today's students with a framework or worldview that values the relevance of religious and biblical studies. This new course (Foundations model) we propose would not attempt to compete with the content coverage of the Old and New Testament survey courses, but rather we would introduce a new concept of teaching religion, which would be thematically-based and require students to learn to articulate a Christian worldview in an intelligent and thoughtful manner. This Christian worldview would be developed throughout the course and based on assumptions, themes, and ways of thinking (issues of hermeneutics) introduced throughout the course. A descriptive recounting of the Foundations model will provide an example of what it means, or rather looks like, to effect religious education and spiritual development in the lives of students at a Christian liberal arts college or university. The Foundations model incorporates six key elements which are as follows: 1. Thematic Organization (not book-by-book survey content) 2. Specialized Workbook Focused on Themes for the Course 3. Weekly Critiques 4. The Final Worldview Paper 5. Integration of the Latest Technology 6. The Role of the Instructor and Peer Mentors.
Keywords: Christian; New Testament; Old Testament; Pedagogy; Religion; Survey; Teaching; Worldview